How did the Covid-19 Pandemic Impact the Life of Patients with Schizophrenia Spectrum Disorders? - O. Nombora; A. Certo; J. Rodrigues; Â. Venâncio (European Psychiatry, 2022)
Introduction Since the first outbreak, the Covid-19 pandemic has had and still has several implications worldwide, particularly in severe mentally ill patients, leading to multiple challenges in their management.